Design and fabrication of an automatic tofu factory liquid waste treatment system for hydroponic nutrients - Jaenudin, Jajang; Sihite, John David; Nurkhamdi (JTTM : Jurnal Terapan Teknik Mesin, 2026)
Tofu, a popular traditional food in Indonesia, produces liquid waste from its production process. This waste, after reducing Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD), can be used as a hydroponic nutrient solution. However, the waste has a relatively high acidity level (low pH), whereas the optimal pH range for hydroponic nutrients is 5.5–6.8. Manual pH control is prone to delays and inaccuracies, which can disrupt plant growth. Therefore, this study designed and built an automated microcontroller-based system to condition the pH of tofu wastewater. The system integrates a pH sensor, solenoid valve, stirrer motor, distribution pump, and an Arduino UNO controller. Testing results show that the system can automatically control pH with a stable neutralization rate, reaching the target pH range within 8–15 minutes depending on the initial waste volume. The pH sensor exhibited an average accuracy of ±0.1 pH units. The solenoid valve activates only when pH ≤ 5.5, while the distribution pump operates within the pH range of 5.5–6.8 and temperature below 30°C. This system has the potential to be applied on a small industrial scale as an appropriate technology for converting tofu wastewater into hydroponic nutrients. This approach enhances process efficiency, reduces manual intervention, and supports circular economy principles by valorizing organic waste.